Nilai-Nilai Lokal dalam Kepemimpinan Kepala Desa di Desa Tanarigella Kecamatan Bua Kabupaten Luwu - Nurhasanah Nurhasanah (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2018)
This study was conducted with the aim to know how the influence of local values on the leadership of Tanarigella village head by looking at the village head’s understanding of local values that include adele (fair), lempu (honest) and getteng (firm) and the application of local values to the leadership of the village head in the field of services in the village of Tanarigella. The type of this research used is deskriptif analysis that give a systematic social overview, factual and accurate about obtained in the field. Data collection used the techniques of observation, interview, and documentation. The results of the research indicate that the village head understands local values that are adele, lempu and getteng. Then teh application of the three local values in the leadership of the village head is implemented in three forms of service, namely publik services in the form of provision of public goods and public service, second development services in the form of physical and non-physical development ant third protection services as the village goverment’s efforts to provide a sense of security and peace to the community.